Ovarian cancer screening in menopausal females with a family history of breast or ovarian cancer - Lai, Tiffany (J Gynecol Oncol, 2016)
OBJECTIVE: To determine whether annual screening reduces ovarian cancer mortality in women with a family history of breast or ovarian cancer. METHODS: Data was obtained from the Prostate, Lung, Colorectal, and Ovarian cancer trial, a randomized multi-center trial conducted to determine if screening could reduce mortality in these cancers. The trial enrolled 78,216 women, randomized into either a screening arm with annual serum cancer antigen 125 and pelvic ultrasounds, or usual care arm. This study identified a subgroup that reported a first degree relative with breast or ovarian cancer. Analysis was performed to compare overall mortality and disease specific mortality in the screening versus usual care arm. In patients diagnosed with ovarian cancer, stage distribution, and survival were analyzed as a secondary endpoint. RESULTS: There was no significant difference in overall mortality or disease specific mortality between the two arms. Ovarian cancer was diagnosed in 48 patients in the screening arm and 44 patients in the usual care arm. Screened patients were more likely to be diagnosed at an earlier stage than usual care patients. Patients in the screening arm diagnosed with ovarian cancer experienced a significantly improved survival compared to patients in the usual care arm; relative risk 0.66 (95% CI, 0.47 to 0.93). CONCLUSION: Screening did not appear to decrease ovarian cancer mortality in participants with a family history of breast or ovarian cancer. Secondary endpoints, however, showed notable differences. Significantly fewer patients were diagnosed with advanced stage disease in the screening arm; and survival was significantly improved. Further investigation is warranted to assess screening efficacy in women at increased risk.